1993
DOI: 10.1093/cvr/27.11.1933
|View full text |Cite
|
Sign up to set email alerts
|

Selective and time related activation of the cardiac renin-angiotensin system after experimental heart failure: relation to ventricular function and morphology

Abstract: Cardiac ACE is activated in the early stage after induction of heart failure and is related to the amount of dysfunction. ACE in the kidney is activated only in the chronic stage. The cardiac renin-angiotensin system therefore already appears to be an important neurohumoral adjustment in the early stage of heart failure and is thereby a suitable target for early intervention by ACE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Several studies suggest that local Ang II concentrations may be exceedingly high in the CHF state. 36,37 In our previous study 28 the effect of Ang II and L-NAME to augment RSNA in normal rabbits was completely abolished by losartan and could not be evoked by D-NAME. In another study carried out in rabbits with CHF, we showed that the AT 1 antagonist L-158,809 augmented baroreflex function when given intravenously.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies suggest that local Ang II concentrations may be exceedingly high in the CHF state. 36,37 In our previous study 28 the effect of Ang II and L-NAME to augment RSNA in normal rabbits was completely abolished by losartan and could not be evoked by D-NAME. In another study carried out in rabbits with CHF, we showed that the AT 1 antagonist L-158,809 augmented baroreflex function when given intravenously.…”
Section: Discussionmentioning
confidence: 89%
“…The effects of the aldosterone receptor antagonist (spironolactone) were independent of changes in mean blood pressure. This form of experimental myocardial infarction in rats has been shown to activate the RAAS (39,51). Spironolactone also has been shown to reduce arterial collagen production, independent of changes in systemic blood pressure in the SHR (6) and in an N G -nitro-L-arginine methyl ester plus ANG II with salt model of hypertension (45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that ACE inhibitors exert their effects primarily by inhibiting tissue ACE, and thereby altering the tissue angiotensin II level [22]. There is accumulating evidence that the cardiac renin-angiotensin system is activated in the left ventricle of ligated rats [23][24][25]. Angiotensin II generated locally may be a mediator of ventricular hypertrophy through its proposed growth-promoting properties, thereby stimulating myocyte hypertrophy and collagen synthesis [26].…”
Section: Discussionmentioning
confidence: 99%